Down‐regulation of miR‐200c attenuates AngII‐induced cardiac hypertrophy via targeting the MLCK‐mediated pathway. Issue 4 (25th January 2019) - Hu, Shan; Cheng, Mian; Guo, Xin; Wang, Shun; Liu, Beilei; Jiang, Hong; Huang, Congxin; Wu, Gang
Abstract: Background: MicroRNAs (miRNAs) have been shown to commonly contribute to cardiac hypertrophy (CH). The aim of this study was to test the hypothesis that miR‐200c plays an important role in the progression of CH by targeting myosin light chain kinase (MLCK/MYLK). Methods and results: Cardiac hypertrophy was induced by aortic banding (AB) in rats. Cellular hypertrophy in neonatal rat cardiomyocytes (NCMs) was induced by AngII treatment. Echocardiography, histology and molecular measurements were used to assess the results of the experiments. The levels of apoptosis and reactive oxygen species (ROS) were also measured. Quantitative real‐time PCR (qRT‐PCR) and Western blotting were used to measure mRNA and protein levels respectively. The present results showed that miR‐200c expression was increased in response to CH both in vivo and in vitro. The down‐regulation of miRNA‐200c by a specific inhibitor markedly ameliorated CH resulting from AngII treatment, and the mRNA levels of atrial natriuretic peptide, brain natriuretic peptide and β‐myosin heavy chain were simultaneously decreased. Notably, minimal apoptosis and ROS accumulation were identified in AngII‐induced hypertrophic cardiomyocytes. Conversely, the up‐regulation of miR‐200c using specific mimics reversed these effects. Mechanistic investigations demonstrated that the MLCK gene is a direct target of miR‐200c; an increase in miR‐200c levels led to a decrease in the expression of MLCK and its downstream effector, p‐MLC2, while miR‐200c inhibition increased the expression of these proteins. Furthermore, inhibiting MLCK impaired the anti‐hypertrophic effects contributions produced by the knockdown of miR‐200c. Conclusion: Our studies suggest that miR‐200c may serve as a potential therapeutic target that could delay hypertrophy. We have also uncovered a relationship between miR‐200c and MLCK, identifying MLCK as a direct mediator of miR‐200c.